Effect of the membrane type and resistance load on the performance of the microbial fuel cell: A step ahead of microbial desalination cell establishment - Jafary, T. (Japan Institute of Energy, 2017)
One of the primary sources of drinking water and for non-potable applications is saline (sea) water. Conversely, a vast amount of wastewater is currently produced that needs to be treated before using or discharging. Ocean sea water is considered to be a raw material used in the desalination process and converted to usable water. In the initial stage of the study, a microbial fuel cell (MFC) with a cation exchange membrane (CEM) and an anion exchange membrane (AEM) were used as separators, in the experiments under different (1, 10, 100 and 1000 Ω) loads of resistance, to measure the efficiency in wastewater treatment and electricity production. The system using a CEM produced the maximum or optimal current of 1.8 mA, a columbic efficiency (CE) of 42 and 80 of chemical oxygen demand (COD) removal at 1 Ω external resistance. While the system running with an AEM achieved a maximum current of 1.8 mA, 40 CE and 77 COD removal at 1 Ω. It highlighted the minimal difference between the performances of the MFC either by using an AEM or CEM. In the second stage of this study, a microbial desalination cell (MDC) used as a novel bioelectrochemical system, was developed by modifying the enriched and optimised MFC system. The MDC was investigated for the desalination of salt water and wastewater treatment. The performance of the MDC with 10 g/l of NaCl salt was measured for desalination of brackish water and COD removal for wastewater treatment, CE and electrical current production. The COD removal of the system was greater than 80, and the percentage of desalination was 100 after running for five days. The MDC system produced a maximum current of 1.3 mA. Therefore, the results from the study confirmed that the MDC was an appropriate technology used for simultaneous desalination and wastewater treatment applications and facilitating the production of green energy.